Efficacy and safety of blood-activating herbs combined with edaravone in the treatment of acute ischemic stroke: A protocol for systematic review and meta-analysis. Issue 48 (2nd December 2022) - Su, Zhuoyi; Zhang, Shuai; Yu, Ziqiao; Jin, Hong; Sun, Weichen; Yang, Ziqi; Zhao, Dexi
Abstract : Background: Although the combination of blood-activating herbs and western drugs has shown advantages in the treatment of ischemic stroke, there is no consensus on the safety and efficacy. This study aimed to systematically evaluate the safety and efficacy of the combination of blood-activating herbs with edaravone (EDA) in the treatment of acute ischemic stroke (AIS). Methods: We will implement the search strategy in 8 English and Chinese databases: Cochrane Central Register of Controlled Trials, Web of Science, PubMed, China National Knowledge Infrastructure, China Science and Technology Journal Database, Wanfang Database, EMBASE and MEDLINE. The search included relevant clinical randomized controlled trials and quasi-randomized controlled trials that had been registered for publication by November 2022. Literature screening, data extraction and quality assessment will be performed by 2 authors. We will assess the risk of bias according to the Cochrane Handbook for Systematic Reviews of Interventions. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method classification will be used to assess the quality of the literature. Meta-analysis was performed using RevMan V.5.4 and STATA 16 software. Results: This study will provide a comprehensive analysis of the current clinical evidence on the application of blood-activating herbs combined with EDA in the treatment of AIS. Conclusion: This study will clarify the safety and efficacy of the combination of blood-activating herbs with EDA in the treatment of AIS.